2011
DOI: 10.1128/aem.00559-11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bla CTX-M -Carrying Plasmids from Escherichia coli Isolates Collected in the BfT-GermVet Study

Abstract: In this study, 417 Escherichia coli isolates from defined disease conditions of companion and farm animals collected in the BfT-GermVet study were investigated for the presence of extended-spectrum ␤-lactamase (ESBL) genes. Three ESBL-producing E. coli isolates were identified among the 100 ampicillin-resistant isolates. The E. coli isolates 168 and 246, of canine and porcine origins, respectively, harbored bla CTX-M-1 , and the canine isolate 913 harbored bla CTX-M-15 , as confirmed by PCR and sequence analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 35 publications
4
23
0
Order By: Relevance
“…The same group also characterized MDR E. coli isolates from hospitalized animals, further illustrating that animal-associated commensal E. coli strains possess a wide array of transferable genetic determinants (11). A similar conclusion was also derived by Schink et al (21) through the study of bla CTX-M-1 genes from E. coli. It is worth noting, however, that the evolution of resistant bacteria varies depending on the antibiotic and in many cases is affected by host and environmental factors as well as the local microbial population.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…The same group also characterized MDR E. coli isolates from hospitalized animals, further illustrating that animal-associated commensal E. coli strains possess a wide array of transferable genetic determinants (11). A similar conclusion was also derived by Schink et al (21) through the study of bla CTX-M-1 genes from E. coli. It is worth noting, however, that the evolution of resistant bacteria varies depending on the antibiotic and in many cases is affected by host and environmental factors as well as the local microbial population.…”
supporting
confidence: 62%
“…Extensive investigation of these organisms enabled the establishment of an in-depth understanding of AR mechanisms and prevalence, and many of the discoveries have broad implications. For instance, Schink et al (21) examined extended-spectrum ␤-lactamase (ESBL) genes in E. coli isolates from companion and farm animals with defined disease conditions. They concluded that the presence of identical bla CTX-M-15 genes in diverse plasmid backgrounds in different members of the Enterobacteriaceae from human and animal sources in different countries highlighted the incredible flexibility of resistance plasmids to undergo structural changes in response to evolutionary needs.…”
mentioning
confidence: 99%
“…coli of ST410 carrying the bla CTX-M-15 gene has been detected in dog urinary samples and human samples in China and other countries [16,[25][26][27]. E. coli of ST648 carrying bla CTX-M-15 gene has been frequently found in clinical ESBL-producing E. coli isolates from humans and animals worldwide [15,16,24,28], and therefore the ESBL-producing E. coli of ST648 is regarded as the potential extended-host spectrum genotype.…”
Section: Discussionmentioning
confidence: 99%
“…They were not only detected in humans (1,2), but also in a broad range of animal species ranging from companion animals (3)(4)(5) to food animals (6-10), and they could also be found in food (11,12). Extended-spectrum ␤-lactamases are plasmid-encoded enzymes that inactivate a large number of ␤-lactam antibiotics, including extended-spectrum and very-broad-spectrum cephalosporins and monobactams.…”
mentioning
confidence: 99%